Pengaruh Inflasi, Transaksi E-money, Industri Besar Sedang, Suku Bunga Terhadap Pertumbuhan Ekonomi - Fatmasari, Dwi; Aji, Tony Seno (Independent: Journal of Economics, 2024)
A country’s economy is not always in a stable condition. At one time the economy grew rapidly continuously and at another time the growth rate slowed. This condition is caused by various factors. These factors include inflation, electronic money transaction activities, large and medium industrial indexes, and interest rates. This research aims to determine whether there is an influence caused by the independent variables (inflation, electronic money transactions, large and medium industry index, and interest rates) on the dependent variable (economic growth). To determine the continuation of the influence on each variable, testing was carried out using a multiple linear regression test. The test results show that the variables inflation, electronic money transactions, large and medium industrial index and interest rates have a significant effect on economic growth.